University–Industry Collaboration: Assessing the Matching Quality Between Companies and Academic Partners - Nisit Manotungvorapun (2020)
IEEE Firms engaged in university–industry collaboration (UIC) desire to advance knowledge and new technologies with their academic partners, however the performance of knowledge creation and transfer is greatly affected by complementarity and compatibility between the firm and academic institute. In practice, many firms assess the appropriateness of academic partners using a broad range of criteria, with high subjectivity. This paper therefore seeks to address this challenge by introducing a systematic approach to help firms determine the appropriateness of academic partners, represented as “matching quality” in this paper. Three facets of matching quality are examined: complementarity of research ability, compatibility in business mindset, and compatibility in relationships. This paper proposes a framework and model for assessing matching quality, along with a case study to demonstrate how the proposed model works.